Unlocking a Circular Economy with Blockchain: Recommendations for Policymakers and Researchers - Bereczk, Ádám; Hódiné Hernádi, Bettina; Mélypataki, Gábor (Theory, Methodology, Practice – Review of Business and Management, 2024)
Blockchain technology can help to build a circular economy in many areas, promoting sustainability and more efficient use of resources. In this paper, we examine the areas where we can expect significant breakthroughs from this technological innovation in the circular economy and the state of the domestic regulatory environment. We then recommend improvements to legislators that can help blockchain and its ecosystems support sustainable development in Hungary.